Primary scrotal melanoma: it is time to destigmatize genital lesions, - Ezgi Özkur; İlknur Kıvanç Altunay (Sociedade Brasileira de Dermatologia, 2020)
Abstract Primary male genital melanomas are very rare; they are associated with high mortality and late detection. Scrotal melanoma is the least common presentation and only 23 cases have been reported. Herein, the authors present a 30-year-old patient with stage IIIC (T4b, N2a, M0) scrotal melanoma in order to report the characteristics, treatment, and outcome, as well as to emphasize the importance of examination of the genitals, education of patients about self-examination and destigmatizing genital lesions to increase the likelihood of earlier detection.